Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.

Silicon oxidation by NAPPES: From dangling bonds to oxygen islands to 2D SiOx layer to the onset of bulk SiO2 formation - Ghosalya, Manoj Kumar; Jain, Ruchi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Valence band and core level photoelectron spectral measurements at near-ambient pressures (NAP; up to 0.5 mbar) were made in the presence of molecular oxygen to explore the various oxidation stages of silicon surfaces. Dangling bonds feature observed on clean Si-surfaces in the valence band at ultrahigh vacuum decreases dramatically due to oxygen adsorption between ambient temperature and up to 400 K at 0.1 mbar of O-2 pressure. The adsorption of oxygen on dangling bonds appears to be localized as islands; this reflects in the surface heterogeneous character and also responsible for the broadening in the oxygen gas phase vibrational features. This is further supported by an increase in the work function and can be correlated to the presence of Hofer (molecular) precursor. When the temperature was increased to 500 K, molecular precursor species dissociates to form Si-=-0 species. This is fully supported by the change in the Si work function as well as from the observation of oxidized Si species from Si 2p core level spectra. At >= 600 K, the Si-=-0 species dissociates to form a uniform 2D oxide layer on the silicon surface, which is characterized by the reappearance of sharp vibration features for gas-phase O-2 molecules. This layer is also quite stable up to 800 K and without any further oxidation in the bulk. On increasing the temperature to 850 K at 0.2 mbar oxygen pressure, bulk Si oxidation begins and the work function increases drastically by 1 eV. An angle-dependent Si 2p spectra recorded map out the presence of elemental Si to Si4+ from bulk to the surface, respectively. A simple model is proposed to show the various stage of silicon oxidation. A continuous change in the work function and electronic states observed due to gas-lattice (O-2-Si) interaction indicates the implications for surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, 2D layered materials.

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science